Interfacial characteristics of titanium coated micro-powder diamond abrasive tools fabricated by electroforming-brazing composite process. (November 2019) - Shen, Jianyun; Li, Longjiang; Wu, Xian; Chen, Hongkun; Huang, Wuzhen; Mu, Dekui
Abstract: In this study, abrasive tools were fabricated by an electroforming-brazing composite process. The abrasive tools were prepared using micro-powder diamond (MPD) grits with and without titanium (Ti) coatings. The interface characteristics of the MPD diamond grits and filler alloy were investigated. The results show that the diamond grits are uniformly dispersed on the surface of the steel substrate without visible agglomeration, and the NiCr filler alloy has good wetting toward diamond grits. Compared to the uncoated diamond grits, the abrasive grains with a Ti coating have an ideal grain distribution and brazed joints, and no aggregation of Si element observed at its edge. There is a more stable carbide TiC that formed on its surface in addition to the chromium carbide. Furthermore, the coated diamond grits are not graphitized and show a better residual stress state. In the abrasive tools with Ti-coated diamond, numerous intermetallic compounds (IMCs) are formed in the brazing layer, but the formation of theγ-Ni-based solid solution is relatively slight. The IMCs increase the microhardness of the filler alloy and help improve the wear resistance of the solder layer. Graphical abstract: Unlabelled Image Highlights: Abrasive tools with monolayer micro-powder diamond grits are prepared by the electroforming-brazing composite process. The interfacial characteristics of Ti-coated and uncoated diamond/Ni-Cr alloy treated under the composite process are compared. The effects of the titanium coating of the diamond surface on the thermal damage of diamond grits, microstructure and hardness of the solder layer are investigated.